Preface - Smith, ATH (Victoria University of Wellington Law Review, 2013)
This article serves as a preface to this special issue of the Victoria University of Wellington Law Review celebrating its 60th anniversary. The author, then the Dean of the Faculty of Law, provides a brief overview of the Law Review's history as well as its current state.